2023
DOI: 10.3390/v15091888
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Clinical Manifestations and Outcomes between Acute Sporadic Hepatitis A and Hepatitis E Infections in Thailand

Sirajuk Khongviwatsathien,
Wajana Thaweerat,
Thanapat Atthakitmongkol
et al.

Abstract: Hepatitis A virus (HAV) and hepatitis E virus (HEV) infections often present as acute hepatitis with prodromal symptoms. These infections, transmitted via the oral–enteral route, constitute significant public health challenges, particularly in developing countries with subpar sanitary systems. The aim of the study was to describe the clinical manifestations, laboratory findings, and outcomes of hepatitis A and hepatitis E infections in Thailand. We conducted a retrospective chart review and analysis of 152 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…241 Interestingly, in one study, the hepatitis E cohort was older with a greater prevalence of comorbidities, such as hypertension, diabetes mellitus, chronic kidney disease, chronic hepatitis B, and postkidney transplantation status, than the hepatitis A cohort. 242 A recent single-center retrospective study from Bulgaria demonstrated that men or women with HEV have 3.091-fold or 5.161-fold greater odds of having "hypertension" comorbidity than those with HAV (p = 0.032 or p = 0.049). 243 Representative factors influencing the severity of hepatitis E are shown in Table 1.…”
Section: Existence Of Metabolic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…241 Interestingly, in one study, the hepatitis E cohort was older with a greater prevalence of comorbidities, such as hypertension, diabetes mellitus, chronic kidney disease, chronic hepatitis B, and postkidney transplantation status, than the hepatitis A cohort. 242 A recent single-center retrospective study from Bulgaria demonstrated that men or women with HEV have 3.091-fold or 5.161-fold greater odds of having "hypertension" comorbidity than those with HAV (p = 0.032 or p = 0.049). 243 Representative factors influencing the severity of hepatitis E are shown in Table 1.…”
Section: Existence Of Metabolic Diseasementioning
confidence: 99%
“…Host factors Older age 163,171 Genetic factors 192,194 Viral factors HEV viral load 174,195 HEV genotype 163,164,195 Nucleotide mutation 172,208 Other factors Existence of chronic liver disease 229,232 Existence of metabolic disease 242,250 Coinfection of HAV 244 Abbreviations: HAV, hepatitis A virus; HEV, hepatitis E virus. women and 41-year-old men) contracted HEV infection through blood transfusion.…”
Section: Items Factorsmentioning
confidence: 99%